From Literacy to Multiliteracy: Validity and Practicality of The Multiliteracy Integrative Learning (MULGRANING) Model - Vivi Indriyani; Herlin Triana; Trisna Helda; Zaiton Zakarya; Hasri Fendi (Yayasan Keluarga Guru Mandiri, 2025)
A learning model capable of integrating various literacies and disciplines is urgently needed to face the challenges of 21st-century learning. This need drives the development of the Multiliteracy Integrative Learning Model (MULGRANING) which focuses on language learning through the integration of various fields of science. This study aims to analyze the validity and practicality of the MULGRANING model. The research method used is research and development (RD) using the Plomp Nieeven model which consists of preliminary research, prototyping stage, and assessment stage. Data were obtained through expert validation and limited trials on teachers and students at the high school level, namely at SMAN 2 Padang and SMAN 9 Padang. The results of the study indicate that the MULGRANING model has high validity in terms of material (92%), presentation (96%), language (84%), graphics (77%), model syntax (88%), social system (90%), reaction principle (84%), support system (91%), instructional and accompanying impact (88%). Furthermore, teachers and students rated this model as practical to implement, with an average student practicality score of 91% and a teacher practicality score of 95%. The model is categorized as very practical because it provides a clear learning flow, varied activities, and allows for the development of language skills and 21st-century skills. Based on these findings, it can be concluded that this model can be used as an alternative in the language learning process.